PERSON WITH DISABILITIES: INCLUSIVE PHYSICAL ACTIVITY&PHYSICAL EDUCATION LITERACY AND GUIDELINES FOR REPORTING AND WRITING BASED ON THE EVIDENCE (Fiep Bulletin - online, 2014)
This study was aimed to investigate the literacy and guideline for reporting and writing about the inclusive physical activity (PA) and physical education (PE) of person with disabilities for quality implantation of education, health and life. It was an historical research in inclusive Physical Activity and Physical Education. The topic was the literacy for reporting and writing about person with disabilities. The paradigm was an intellectual device that contains a scholar’s beliefs and assumptions about the world, the past and the evidence (Struna NL , 2009). The data was based on the sources hierarchical system: primary (UN -Declaration of human rights of person with disabilities; WHO -IC D10/ICF ; UNESCO - Chart of PE and sport) and secondary (academic articles, chapters books, media and multimedia documents). The data analysis was based on Historical criticism (external/authenticity and internal/credibility of the sources). The data showed the appropriate: 1. terminology (person with… disabilities, learning disabilities, quadriplegia, autism, trisonomia 21 syndrome; visually impaired, deaf…) 2. portrayal issues (focus on person; emphasize on the skills, abilities; inclusive society and education…) The literacy and guideline, for reporting and writing about the inclusive physical activity (PA) and physical education (PE) of person with disabilities, was the opportunity to build:• the dignity of person with disabilities versus the dignity of all the perso,;• the culture of inclusive PA&PE versus the inclusive society,• the sharing specific langue versus society of knowledge,• the sharing knowledge versus networking research all over the world,• the networking research versus the multilevel cooperation (academic, professional…,• the networking/ multilevel knowledge versus the implementation of quality of education, health and life of all the person.
Keywords: Person with disabilities; inclusive PA&PE; literacy&guideline; reporting&writing